Arcx Tech & Enterprise ordering systems with collaborative filtering / Ihsan Ismail - Ismail, Ihsan (2021)
Arcx Tech & Enterprise founded by En. Ismadi Bin Ismail in November 2016. The business does sales on new and refurbished PC, notebook, printer, cable, toner and accessories. Currently, the business does promoting on Facebook and Whatsapp. Any order received will be stored in either wave apps or excel form. Due to the different location of order storage, the process needed to trace back the order became tedious. It is time-consuming to search for an order with two different storage point. Next problem, Customer lost interest to buy the product promoted by the stakeholder because there is lack of information regarding the product review or rating. Therefore, this project created with the aims to develop Arcx Tech & Enterprise Ordering System (ATEOS) with collaborative filtering. The methodology used in this waterfall is iterative waterfall model. This model includes three phases, which are requirement gathering, and analysis phase, design phase, and implementation phase. Interview and gathering relevant records method are the collection method to gather requirement. In the requirement analysis phase, all the requirements will be analysed by using CRUD Technique that consists of “create”, “read”, “update”, and “delete”. Then, several diagram will be constructed and compiled in Software Requirement Specifications (SRS). Based on the discussion on the three type of recommendation system, which is content-based, collaborative and hybrid filtering, collaborative filtering based on product is chosen for this project. This system function is to recommend to the user several top sell product table for each category. In the design diagram, storyboard will be developed and several diagram will be constructed and compiled in Software Design Document (SDD). The last phase which is implementation phase, ATEOS will be developed. In recommendation for future work, several improvement could be made to ATEOS in the future such as implement several payment method and implement sent activation link or reset password link to real email account.